To Capture Personnel Spiritual Belief of the Nursing Students (Global Journal of Management and Business Research, 2021)
Background: Science gets impact on physical health. #x201C;Science gets us physical comforts, spirituality brings us mental calm#x201D;. Dalai lama 2006. The meaning of spirituality and spiritual care among nurses is culturally constituted and influenced by many factors such as the nurse#x2019;s ethnic background, religious affiliation, level of education and clinical experience. Spiritual care is a recognized field in nursing (Bald acchino 2006) and an element of quality nursing care (Mc Even 2005). Many scientific studies have shown that when meditation and chanting is done in groups it has more benefits than when done individually. (Dr. K.K Aggarwal, 2017) Method: This study capture lived spiritual experience of 50 self selected nursing students who identified spiritual belief and needs in patient using a phenomenological approach data is collected by five open ended question through Interview schedule. Participants were first Year nursing student#x2019;s novice to profession, studying the diploma course in nursing was chosen as the study sample. Results: Analysis of the data indicated that spiritual experiences could occur in a range of four themes-Spiritual beliefs, providing spiritual care, meeting Spiritual needs and emphasis of spiritual initiative into Nursing Education could be triggered by catalysts such as nature or newness, evoked responses including awe and appreciation, and led to outcomes of connection, awareness, growth and freedom. Conclusion: In the present study, the nursing student had shown acceptance towards spiritual health and understanding the experience of spiritual belief in nursing students can help to improve the comfort level in meeting patient needs and has impact on quality patient care.
Keywords: spiritual belief; lived experience; nursing students